(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The acromian process of scapula is project forward from lateral end of spinous process of scapula. Coracoacromial ligament is extend between coracoid process and acromian process ,it help in formation of coracoacromial arch, anatomy of this region is important for better understanding of pathology regarding subacromial bursa ,impingement syndrome . Materials and Methods: Present study was carried out on 74 dry, adult human scapulae 38 left side and 36 right side from teaching collection of anatomy department ,sex of the specimen not known ,Scapular length, width ,acromian process length ,width, thickness ,coracoacromial distance ,acromioglenoid distance was measured with the help of vernier caliper, we also found different shape of acromian process. Results: We observed 74 scapula out of them 38 scapula are of type –I which was 51.35%,13 scapula of type –II which was 17.57%, 23 scapula of type –III which was 31.08%, we observed mean value acromian length was 4.50±0.52cm, width of acromian process was 2.10±0.26cm, thickness of acromian process was 0.78±0.10cm ,acromicoracoid distance was 3.45±0.53cm, distance between acromian process and supraglenoid tubercle was 2.48±0.40cm. Conclusion: These findings suggest that the difference in various parameters related to acromian process help in better understanding of anatomy and pathology of coracoacromial arch ,rotator cuff and also helpful to other clinician.